Resveratrol solid lipid nanoparticles to trigger credible inhibition of doxorubicin cardiotoxicity - Zhang L (Dove Medical Press, 2019)
Lili Zhang,1 Kexin Zhu,1 Hairong Zeng,2 Jiaxin Zhang,1 Yiqiong Pu,3 Zhicheng Wang,4 Tong Zhang,3 Bing Wang1,51School of Pharmacy, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Pharmacy, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Experiment Center for Teaching and Learning, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 4Department of Laboratory Medicine, Huashan Hospital, Shanghai Medical College, Fudan University, Shanghai, People’s Republic of China; 5Center for Pharmaceutics Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People’s Republic of ChinaBackground: Doxorubicin (DOX), a broad-spectrum chemotherapy drug, is clinically employed to treat cancers especially for breast cancer and lung cancer. But its clinical applications are limited by the dose-dependent cardiac toxicity. Resveratrol (Res), a polyphenolic antitoxin, has been proved to be capable of improving the cardiomyocyte calcium cycling by up-regulating SIRT-1-mediated deacetylation to inhibit DOX-induced cardiotoxicity.Purpose: The objective of this study was to develop a solid lipid nanoparticle (SLN) loaded with Res to trigger inhibition of DOX-induced cardiotoxicity.Methods: Res-SLN was prepared by emulsification-diffusion method followed by sonication and optimized using central composite design/response surface method. The Res-SLN was further evaluated by dynamic light scattering, transmission electron microscopy for morphology and high performance liquid chromatography for drug loading and release profile. And the Res distribution in vivo was determined on rats while the effect of inhibit DOX-induced cardiotoxicity was investigated on mice.Results: Res-SLN with homogeneous particle size of 271.13 nm was successfully formulated and optimized. The prepared Res-SLN showed stable under storage and sustained release profile, improving the poor solubility of Res. Heart rate, ejection fractions and fractional shortening of Res-SLN treating mice were found higher than those on mice with cardiac toxicity induced by single high-dose intraperitoneal injection of DOX. And the degree of myocardial ultrastructural lesions on mice was also observed.Conclusion: Res-SLN has a certain therapeutic effect for protecting the myocardium and reducing DOX-induced cardiotoxicity in mice. Keywords: resveratrol, solid lipid nanoparticles, doxorubicin, heart failure